1996
DOI: 10.1242/dev.122.12.3881
|View full text |Cite
|
Sign up to set email alerts
|

eFGF, Xcad3 and Hox genes form a molecular pathway that establishes the anteroposterior axis in Xenopus

Abstract: Classical embryological experiments suggest that a posterior signal is required for patterning the developing anteroposterior axis. In this paper, we investigate a potential role for FGF signalling in this process. During normal development, embryonic fibroblast growth factor (eFGF) is expressed in the posterior of the Xenopus embryo. We have previously shown that overexpression of eFGF from the start of gastrulation results in a posteriorised phenotype of reduced head and enlarged proctodaeum. We have now det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…These results support the idea that FGF signaling is actively involved in posterior formation rather than in the anterior. Additional gain of function studies also in Xenopus drew similar conclusions; these were with overexpression of eFGF reported to induce a posteriorized phenotype with enlarging proctodeum and elevated expression level of posterior genes xcad3, hoxB9, and hoxA7 [125,171]. In these instances of upregulation of posterior genes, the anterior specific factors were suppressed and resulted in small or truncated head formation [125,171].…”
Section: The Ap Axismentioning
confidence: 62%
See 2 more Smart Citations
“…These results support the idea that FGF signaling is actively involved in posterior formation rather than in the anterior. Additional gain of function studies also in Xenopus drew similar conclusions; these were with overexpression of eFGF reported to induce a posteriorized phenotype with enlarging proctodeum and elevated expression level of posterior genes xcad3, hoxB9, and hoxA7 [125,171]. In these instances of upregulation of posterior genes, the anterior specific factors were suppressed and resulted in small or truncated head formation [125,171].…”
Section: The Ap Axismentioning
confidence: 62%
“…Both genes family of caudal homologs and Hox have been reported as the targets of FGF and Wnt signaling during AP elongation in vertebrates [125,171,[176][177][178]. However, a growing body of evidence indicate that FGF signaling is not a solo regulator of AP patterning.…”
Section: The Ap Axismentioning
confidence: 99%
See 1 more Smart Citation
“…In light of their ancient and fundamental roles in regulating morphogenesis and A-P patterning, the amplification and divergence of Hox complements in vertebrates is thought to be a driver in the emergence of new traits and evolutionary novelties by being integrated in gene regulatory networks underlying morphological diversity [2,62,77,78] Diverse molecular and cellular mechanisms are thought to contribute to the regulation and generation of collinear domains of Hox expression [20,21,[79][80][81][82][83][84][85][86]. Experimental studies in a wide range of vertebrates and invertebrates have revealed that collinear Hox expression arises in part through the ability of Hox clusters to integrate information from A-P signaling centers in response to cues from major signaling pathways, such as retinoic acid (RA), fibroblast growth factor (FGF), and Wnts [21,[87][88][89][90][91][92][93]. For example, in vertebrate model systems, opposing gradients of RA and FGFs have been shown to regulate nested domains of Hox expression in the CNS and in mesodermal domains that control specification of vertebral identities and axial elongation (Figure 1a,b) [91,[94][95][96][97][98][99].…”
Section: Introductionmentioning
confidence: 99%
“…During early vertebrate development, FGF signaling is crucial for the induction of mesoderm and endoderm, neural fate specification, axial polarity and morphogenetic movements (Böttcher and Niehrs, 2005). Studies in Xenopus have first demonstrated a role of FGFs in the induction and migration of mesoderm during trunk and tail development (Slack et al, 1996). In chick and Xenopus embryos, FGFs participate in the induction of neural fate (Hongo et al, 1999;Streit et al, 2000;Wilson et al, 2000;Hardcastle et al, 2000;Pera et al, 2003, De Robertis and).…”
Section: Fibroblast Growth Factor Signalingmentioning
confidence: 99%